Tenure reform for better forestry: An unfinished policy agenda - Aggarwal, S.; Larson, A.M.; McDermott, C.; Katila, P.; Giessen, L. (Elsevier, 2021)
The global community is currently grappling with multiple and overlapping social and environmental threats. These include the climate emergency, COVID-19 and the threat of widespread hunger, and the accelerating loss of biodiversity. All of these threats point to an urgent need to restore and sustainably manage land and forests. Studies are pointing to the critical role of tenure reform, and in particular strengthening collective forest tenure, as an effective means to reduce deforestation, mitigate climate change, restore ecosystem services and maintain biodiversity. Since the 1970s, countries worldwide have attempted to better recognize the customary rights of local communities. Yet despite over 40 years of effort, collective forest tenure reforms have yielded only moderate results. This article draws on recent assessments conducted in 23 countries by the Food and Agriculture Organization of the United Nations (FAO) on community-based forestry and associated forest tenure regimes based on the internationally endorsed Voluntary Guidelines on the Responsible Governance of Tenure (the VGGT). The findings suggest that governments are increasingly giving legal recognition to community rights to use both timber and non-timber forest products for commercial purposes. Yet, the tenure provided to collective forestry is less robust than that held by companies and smallholders in a number of ways. These include fewer legal protections, more barriers to the use of these rights, inadequate access to justice, and less administrative support in documenting rights. Furthermore, in many cases the existing community forestry legal provisions are not implemented. The relatively successful cases suggest that with robust tenure, communities and smallholders can be potent vehicles for moving towards sustainable forest management and mitigating climate change, improving local livelihoods, contributing to timber and non-timber product economies, and achieving several of the Sustainable Development Goals. But for this, governments will need to strengthen community and local rights within their legal frameworks and mainstream implementation in government policies and practices. Non-governmental organizations, civil society organizations, donors, research institutions and academia can provide important support through policy implementation, research, and ensuring inclusive policy formulation processes.